E-040 Flat panel imaging of occlusion site and collateral scores for emergent large vessel occlusion. (23rd July 2017) - Elijovich, L; Choudhri, A; Inoa-Acosta, V; Arthur, A; Hoit, D; Nickele, C; DiNitto, J
Abstract : Introduction: Flat Panel Imaging in the angiographic suite for patients with Emergent Large Vessel Occlusion (ELVO) can be acquired immediately prior to mechanical thrombectomy (MT). This can identifying patients who no longer need MT after long time delays or due to reperfusion with IV TPA. Additionally, these techniques may allow the angiography suite to serve as the initial diagnostic modality and treatment location for patients with ELVO. We performed a correlative study on patients who had received both acute stroke CT Angiography (CTA) and Flat Panel CTA (FP-CTA) to determine agreement on the site of occlusion and CTA collateral score (CS) in patients with ELVO. Methods: This is a prospective pilot study of consecutive patients treated at a comprehensive stroke center. Patients with ELVO who underwent MT were studied with CTA in the emergency department on a Lightspeed VCT (GE Medical Systems). FP-CTA was then acquired before MT via an aortic arch pigtail injection. Post processing of images was performed on one of two interventional C-Arm CBCT systems: Siemens Artis Q Biplane or Zeego (Siemens Healthcare AG, Forchhiem Germany). Slice thickness was matched to ER CT thickness. Patient baseline characteristics and details of treatment and outcome were retrospectively collected. A blinded neuroradiologist read all paired CTA and FP-CTA datasets. Site of occlusion and the CS were rated and correlated. A change is CS between CTA and FP-CTA was defined as a greater than two point change. Time between CTA and FP-CTA acquisition was also recorded. Results: Ten patients (mean age 60.8 years, NIHSS 17, 60% Female) were included in the study. IV TPA was administered to 70% of patients. There was 100% correlation of the site of occlusion: 8 MCA, 1 ICA, 1 Basilar. Average time between CTA and FP-CTA was 102 min (range 76–121). There was 90% correlation on CTA and FP-CTA CS with only a single patient with a 2 point decrease in CS. Conclusion: FP-CTA correlates well with standard CTA in determining site of occlusion and CS in the setting of ELVO. This angiographic tool may have potential applications for both triage and patient selection of patients with ELVO. Disclosures: L. Elijovich: 1; C; Siemens. 2; C; Stryker, Codman, Medtronic, Microvention, Penumbra. A. Choudhri: None. V. Inoa-Acosta: None. A. Arthur: 1; C; Siemens. 2; C; Microvention, Codman, Penumbra, Stryker, Medtronic. 4; C; Cerebrotech, Synchron. D. Hoit: 2; C; Medtronic, Microvention. C. Nickele: 1; C; Microvention. J. DiNitto: None.